Genetic variations and plasma levels of gelatinase A (matrix metalloproteinase-2) and gelatinase B (matrix metalloproteinase-9) in proliferative diabetic retinopathy - Beránek, Michal; Kolář, Petr; Tschöplová, Svatava; Kaňková, Kateřina; Vašků, Anna (Molecular vision, 2008)
PURPOSE: Matrix metalloproteinases (MMPs) are postulated to be involved in the development of retinal angiogenesis through the regulation of extracellular matrix. The objective of the present study was to test for a possible association of five single nucleotide polymorphisms (SNPs) in the MMP-2 gene and two polymorphisms in the MMP-9 gene with proliferative diabetic retinopathy (PDR) and to determine their plasma levels. METHODS: The study comprised 490 Caucasian participants, who were divided into three groups: diabetics with PDR, diabetics without PDR, and nondiabetics. Genotypes were detected by polymerase chain reactions followed by restriction analyses with specific endonucleases and their frequencies determined. Plasma levels of MMP-2 and MMP-9 proteins were analyzed by ELISA. RESULTS: Neither MMP-2 SNPs nor MMP-9 SNPs revealed significant association with PDR in single-locus comparisons; similarly, MMP-2 haplotype frequencies did not differ notably between groups, although the C-allele of the -1306C/T polymorphism and the C-allele containing haplotype (CGCG) in MMP-2 exhibited marginally significant association with PDR in males (p<0.05, p(corr)=NS). Both MMP-2 and MMP-9 plasma levels showed statistically significant differences among the studied groups (p<0.001 and p=0.001, respectively) with highest levels in the PDR group. MMP-2 plasma levels were markedly higher in carriers of either the -1306CC and -1306CT genotypes and (p=0.009) or CGCG haplotype (p=0.043). CONCLUSIONS: These findings indicate that genotype- and haplotype-specific effects on MMP-2 expression corresponding with its plasma levels may contribute to the susceptibility to PDR.
Keywords: haplotypy; Humans; diabetická retinopatie; lidé středního věku; Disease Progression; Female; Aged; dospělí; financování organizované; Haplotypes; Financing, Organized; senioři; lidé; genetická variace; Genetic Variation; Adult; ženské pohlaví; Matrix Metalloproteinase 9; Male; Middle Aged; matrixová metaloproteinasa 9; Sex Characteristics; Diabetic Retinopathy; matrixová metaloproteinasa 2; pohlavní dimorfismus; progrese nemoci; mužské pohlaví; Matrix Metalloproteinase 2